2000
DOI: 10.1097/00005344-200005000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Radical System in Chronic Infarcted Rat Heart: The Effect of Combined Beta Blockade and ACE Inhibition

Abstract: In vitro experiments suggest that beta blockade and angiotensin-converting enzyme (ACE) inhibition may protect the failing heart by reduction of myocardial oxidative stress. To test this hypothesis in an in vivo model, the beta blocker metoprolol (350 mg) and the ACE inhibitor ramipril (1 mg) were given either alone or in combination to rats (per kilogram body weight per day) for 6 weeks after myocardial infarction. Left ventricular end-diastolic pressure (LVEDP), contractile function of papillary muscles, enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Hill and Singal (1996) evaluated antioxidant enzyme activities and oxidative stress in the myocardium for 16 weeks after myocardial infarction in rats, and found that SOD, GPx and CAT activities decreased gradually but significantly 4 weeks after myocardial infarction, in tandem with the continuing increase in TBARs. Such results were similar to those found by Theres et al (2000). Our findings combined with those studies give a clear picture of the changes in the endogenous antioxidant system under conditions of oxidative stress.…”
Section: Discussionsupporting
confidence: 92%
“…Hill and Singal (1996) evaluated antioxidant enzyme activities and oxidative stress in the myocardium for 16 weeks after myocardial infarction in rats, and found that SOD, GPx and CAT activities decreased gradually but significantly 4 weeks after myocardial infarction, in tandem with the continuing increase in TBARs. Such results were similar to those found by Theres et al (2000). Our findings combined with those studies give a clear picture of the changes in the endogenous antioxidant system under conditions of oxidative stress.…”
Section: Discussionsupporting
confidence: 92%
“…However, in AngII-treated rat cardiac fibroblasts, the activity of both MnSOD and Cu/ZnSOD was inhibited, and expression of MnSOD, but not Cu/ZnSOD, was decreased (59). Similarly, in rats subjected to MI, MnSOD expression in the infarct area and activity of both MnSOD and Cu/ZnSOD were reduced, and these decreases were suppressed by treatment with RAS inhibitors (127). In addition, nuclear SIRT1, which is increased in cardiomyocytes in several models of HF, upregulates MnSOD expression, leading to a reduction in ROS levels and apoptosis in AngII-treated C2C12 cells, as well as improved cardiac function and survival in hamsters with chronic HF (126).…”
Section: Antioxidant Downregulationmentioning
confidence: 97%
“…Both the favorable alteration of the LV loading condition and suppression of the renin-angiotensin system by ACE inhibitors might attenuate LV remodeling and play an important role in the treatment of heart failure after MI. In addition, changes in cardiac gene expression, 46) and a reduction of myocardial oxidative stress 47) by ACE inhibitors have been reported. Some methodological limitations deserve comment when interpreting the present results.…”
Section: Discussionmentioning
confidence: 99%